Amniotic band syndrome. Case report and review of the literature. - Phiske, M.M.; Sawalka, S.S.; Shetty, G.J.; Jerajani, H.R. (European Journal of Pediatric Dermatology, 2006)
Amniotic band syndrome (ABS), occurring in approximately 1:1,200/15,000 live births, of unknown etiology, is characterized by an asymmetric destructive fetal process initiated by rupture of amnion, causing the fetus to become adherent to, intertwined in, and tethered by fibrous mesodermic bands. Distortion of fetal anatomy leads to limb, cranial or body wall defects occurring as the fetus grows with cranio-facial defects being associated with increased mortality during newborn period. Three cases of amniotic band syndrome with constricting bands, shortening of digits, autoamputation and syndactyly were seen. One case had encephalocele at birth, delayed milestone, low intelligence quotient, frontal bossing, depressed nasal bridge, low set ears and club foot. Additional coincidental findings associated with the cases were scabies and atopic dermatitis. Our cases highlight the varied spectrum of presentation of the syndrome ranging from mild to one with systemic involvement, but leading normal life.